Evolution of contemporary museum architecture - Bilous, Yulia (Видавництво Львівської політехніки, 2013)
This article deals with the development of museum architecture from the formation of the classic building architecture to the establishment of the contemporary museum architecture. Changes in the museum building architecture and displaying principles have been analysed. The 19th century was defined by the emergence of a vast number of museums serving through present as examples of the contemporary museum architecture. New styles are tried in the museum architecture along with changes in art trends which facilitates the development of the museum architecture as an individual work of art.
Keywords: museum; art; development of museum architecture